2022
DOI: 10.1186/s12964-022-00991-4
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell and bulk RNA sequencing reveal ligands and receptors associated with worse overall survival in serous ovarian cancer

Abstract: Background Serous ovarian carcinoma is the most frequent histological subgroup of ovarian cancer and the leading cause of death among gynecologic tumors. The tumor microenvironment and cancer-associated fibroblasts (CAFs) have a critical role in the origin and progression of cancer. We comprehensively characterized the crosstalk between CAFs and ovarian cancer cells from malignant fluids to identify specific ligands and receptors mediating intercellular communications and disrupted pathways rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 116 publications
0
7
0
Order By: Relevance
“…We identified 5 primary signaling pathways in both zebrafish ( Figure 5A ) and neonatal mice Fb/Epi cells ( Figure 5B ), among which 4 signaling molecules are associated with reparative macrophages, including Csf1 , 57 , 58 Cxcl12 , 59 Angptl4 , 60 and Mdk 61 pathways. In macrophages, we identified expression of Csf1r , 57 Sdc4 , 62 , 63 and Cxcr4 64 as the primary receptors of these signals. We noticed that the CSF signaling pathway was highly specific in outgoing signals from Fb/Epi cells to macrophages compared to other signaling pathways from mesodermal/endothelial/endocardial (Mes/EC/Endo) cells ( Figures 5C and 5D ).…”
Section: Resultsmentioning
confidence: 99%
“…We identified 5 primary signaling pathways in both zebrafish ( Figure 5A ) and neonatal mice Fb/Epi cells ( Figure 5B ), among which 4 signaling molecules are associated with reparative macrophages, including Csf1 , 57 , 58 Cxcl12 , 59 Angptl4 , 60 and Mdk 61 pathways. In macrophages, we identified expression of Csf1r , 57 Sdc4 , 62 , 63 and Cxcr4 64 as the primary receptors of these signals. We noticed that the CSF signaling pathway was highly specific in outgoing signals from Fb/Epi cells to macrophages compared to other signaling pathways from mesodermal/endothelial/endocardial (Mes/EC/Endo) cells ( Figures 5C and 5D ).…”
Section: Resultsmentioning
confidence: 99%
“…Compared with YTHDF2 -low macrophages, YTHDF2 -high macrophages exhibited pro-tumoral characteristics with multiple malignancy-promoting signals involved, such as RARRES2, MDK-SDC4/SDC2, CX3CL1-CX3CR1, COL4A5, COL4A2, COL4A1, C3AR1, TNFRSF1A, LILRB1, CCL5, ITGAV, SDC4, CD36, CD47, NRP1, and NRP2 ( Figures 5 A–5C). 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 In particular, some prominent pro-tumoral molecules 31 including MSR1, CCL18, STAB1, CD163L1, MERTK, AXL, GPNMB, and CHI3L1 were highly expressed by YTHDF2 -high macrophages while some prominent anti-tumoral ones 31 including IL1B, CCL2, CCL3, CCL4, TNF, CXCL2, and SOCS3 were highly expressed by YTHDF2 -low macrophages ( Figure 5 D). In summary, our observations demonstrate the pro-tumoral tendency of YTHDF2 -high macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, these cell types, including CAFs, Tregs, M2-TAMs, and MDSCs, have been recognized as biomarkers associated with T-cell exclusion within the tumor microenvironment (TME) [ 56 59 ].The interaction between CAFs and CD47 involves the receptor THBS2/THBS3 on CAFs interacting with CD47 expressed on cancer cells, promoting further cancer progression. Another receptor on the cell membrane of CAFs, MDK, interacts with NCL/SDC2/SDC on cancer cells, potentially serving as therapeutic targets [ 60 ]. Regarding the current understanding of the relationship between regulatory T cells (Tregs) and CD47, research has indicated that the ligand of CD47, SIRPγ, is expressed on T cells and varies with differentiation.…”
Section: Discussionmentioning
confidence: 99%